Less is more for laparoscopic ultrasound-guided liver resection for hepatocellular carcinoma - Gianotti, Luca; Famularo, Simone (Laparoscopic Surgery, 2018)
Despite surgical resection is the treatment of choice for hepatocellular carcinoma (HCC), long-term prognosis remains unsatisfactory with rate of recurrence of approximately 50% at 3 years and more than 70% at 5 years (1,2).